Aggregation-Induced Emission : Applications in Biosensing, Bioimaging and Biomedicine. (Aggregation-Induced Emission, 2022)
This two volume set introduces the up-to-date high-tech applications of Aggregation-Induced Emission (AIE) luminogens mainly in the areas of biosensing, bioimaging, and biomedicine. The 1st volume covers the applications of AIE materials in biosensing and bioimaging, including the technological utilizations in ionic/biomolecular sensing, bacterial imaging, cell imaging, intracellular microenvironment analysis, advanced optical imaging and multimodality, etc. It is an essential reference for materials scientists, chemists, physicists and biological chemists.